THE GENUS FIDENA WALKER 1850IN ARGENTINA AND CHILE (DIPTERA: TABANIDAE) (Acta Entomológica Chilena, 2022)
The genus Fidena inelude 86 species, 10 of them live in Argentina of which F. atripes and F. m o ñ o arein common with Chile. The following subgenera F. (Fidena) species: abominata, Philip 9» Cf, atripes (vonRoeder) 9. latifrons Kroeber 9, Cf, longipalpis Enderlein 9» C?, neglecta Kroeber 9, Cf, nigripes (von Roeder)9. Cf, ochrapogon Wilkerson 9, opaca (Bréthes) 9, CF, sorhens Wiedemann 9, Cf, and from subgenera F.(Leptofídena) haywardi Philip 9 and moño van der Wulp 9, Cf, are redescribed; illustrations, geographicdistribution and female keys are included. A new species Fidena philipi (9) is described; F. atripes, latifrons,neglecta, nigripes and ochrapogon are for the first time mentioned for Argentina; the males describedwere unknown before.
Keywords: Horseflies, Fidena, Argentina, Chile, Taxonomic Revisión